The Festival Order – Music Stages of Power and Pleasure - Miroslava Lukić-Krstanović (University of Belgrade, 2016)
Music festivals consist of a complex of interactions and social and cultural experiences. This paper analyzes music festivals in SE Europe in their function as a planetary prouction, combining regional cross-cultural perspectives and local politics. At the beginning of the 1990s music events in SE Europe (concerts, festivals, cultural happenings) were either a part of political conflict, antagonisms and economic crises, or they were included in the music world through the cultural contacts of global achievements – the music net and industry. Music festivals become the arena and scene of a contradictory reality in these places, being made up of individual, group interests, needs, establishment strategy and politics. To illustrate this phenomenon the paper presents the biggest festivals and spectacles in Serbia and SE Europe: EXIT festival (Novi Sad) attracted thousands of techno and rock lovers with the participation of many famous bands; and the folk trumpet playing festival (Guča), which each summer for several decades has been attracting thousands of lovers of ethno sound to a fair-carnival atmosphere. This ethnological research stresses complex property divisions – lifestyle, music genres, political strategies, scene movements and economic interests.